The role of sustainability reporting in the agri-food supply chain - Topp, Jessie Marie (Kansas State University, 2015)
Agricultural sustainability is a growing concern for the general public because of agriculture’s considerable use of land, water, and other natural resources. In response to this growing concern, companies have started to publish sustainability reports to highlight sustainable practices. The purpose of this study was to examine the role of sustainability reporting from companies in the agri-food supply chain. The research objectives of this study were (1) determine the prevalence of sustainability reporting among food system companies, (2) identify, to what extent, the three components of the triple bottom line model are represented in sustainability reports, (3) determine if/how sustainability reporting differs among sectors of the agriculture supply chain, (4) assess how companies describe stakeholder engagement in sustainability reports, and (5) explore which aspects of reputation are included in sustainability reports. In total, 66 agribusinesses were included in this study of which 16 had published sustainability reports. Data for the quantitative content analysis were collected using a scorecard based on the Global Reporting Initiative (GRI) guidelines. Results indicated that sustainability reporting is limited among companies involved in the agriculture and food supply chain. Though better than sectors studied in previous research, agribusinesses also struggle to explain stakeholder engagement and need to focus sustainability report content to align more closely with the three components of the triple bottom line model – environment, economic, and social.
Keywords: Sustainability reporting; Agri-food supply chain; Agricultural sustainability; Triple bottom line; Reputation management; Stakeholder theory; Agriculture, General (0473); Communication (0459); Sustainability (0640)